2004
DOI: 10.1016/j.virol.2004.03.031
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of SARS coronavirus by a short hairpin RNA expression plasmid targeting RNA-dependent RNA polymerase

Abstract: Severe acute respiratory syndrome (SARS) is a highly contagious and sometimes a lethal disease, which spread over five continents in 2002-2003. Laboratory analysis showed that the etiologic agent for SARS is a new type of coronavirus. Currently, there is no specific treatment for this disease. RNA interference (RNAi) is a recently discovered antiviral mechanism in plant and animal cells that induces a specific degradation of double-stranded RNA. Here, we provide evidences that RNAi targeting at coronavirus RNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 24 publications
(26 reference statements)
3
42
0
1
Order By: Relevance
“…The PCR product was digested with BamHI and EcoRI and ligated to MSCV-PGKpuro (BD Biosciences Clontech) digested with BglII and EcoRI. UbcH8 knockdown experiments were performed by transiently expressing an shRNA construct for cells (29). To test the efficiency of UbcH8 shRNA in cotransfection experiments, 293T cells were transfected with MSCV-UbcH8 shRNA, pFlagCMV2-UbcH8, pCAGGS-mISG15, and pCAGGS-HA-hUBE1L.…”
Section: Methodsmentioning
confidence: 99%
“…The PCR product was digested with BamHI and EcoRI and ligated to MSCV-PGKpuro (BD Biosciences Clontech) digested with BglII and EcoRI. UbcH8 knockdown experiments were performed by transiently expressing an shRNA construct for cells (29). To test the efficiency of UbcH8 shRNA in cotransfection experiments, 293T cells were transfected with MSCV-UbcH8 shRNA, pFlagCMV2-UbcH8, pCAGGS-mISG15, and pCAGGS-HA-hUBE1L.…”
Section: Methodsmentioning
confidence: 99%
“…In other words, BmCPV-RDRP functions as both replicase and transcriptase. Molecular therapy of some human viral disease by dsRNA interference are targeted to RDPD, including RNA viruses such as SARS virus (Lu et al, 2004) and hepatitis virus (McCaffrey et al, 2003). Most studies on anti-virus transgenic animals and plants are also targeted to RDRP genes (Ahlquist, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Viral RdRp plays an essential role in viral RNA replication. Many researchers have shown that siRNA/shRNA targeting the RdRp coding gene could efficiently inhibit viral replication; moreover, according to their reports, viral inhibition triggered by siRNA/shRNA targeting the RdRp gene seems more efficient compared to other genes within the same genome (Ge et al, 2003;Lu et al, 2004;Wang et al, 2004). Therefore, the RdRp gene of TGEV, which is highly conserved among different strains, was employed as an RNAi target in this study, and our results demonstrated that two shRNAs generated from it both blocked viral replication with very high efficiency.…”
Section: Discussionmentioning
confidence: 99%